2018
DOI: 10.1038/s41598-018-28906-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Fibulin-3 knockdown inhibits cervical cancer cell growth and metastasis in vitro and in vivo

et al.

Abstract: To explore the function of fibulin-3 in cervical carcinoma malignant cell growth and metastasis, fibulin-3 expression in normal cervical tissue, cervical intraepithelial neoplasia (CIN), and cervical carcinoma were evaluated by immunohistochemistry. Quantitative real-time-polymerase chain reaction, western blotting, and immunocytochemistry were performed to assess the expression of fibulin-3 at mRNA and protein levels in different invasive clone sublines. Fibulin-3 shRNA and fibulin-3 cDNA were used to transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“… 36 Che et al 37 have suggested that TRIP4 can facilitate tumor growth and metastasis and modulate radiosensitivity of cervical cancer via activating PI3K/AKT pathway. Li et al 38 have indicated that fibulin-3 could promote cervical cancer cell growth and metastasis by activating PI3K/AKT/mTOR pathway. In addition, the GSEA demonstrated that the inhibitory role of ADRA2A in cervical cancer was closely related to the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Che et al 37 have suggested that TRIP4 can facilitate tumor growth and metastasis and modulate radiosensitivity of cervical cancer via activating PI3K/AKT pathway. Li et al 38 have indicated that fibulin-3 could promote cervical cancer cell growth and metastasis by activating PI3K/AKT/mTOR pathway. In addition, the GSEA demonstrated that the inhibitory role of ADRA2A in cervical cancer was closely related to the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti-PD-1 antibody combined with paclitaxel can inhibit extracellular regulated kinase (ERK) and PI3K-Akt signaling pathway and further inhibit the expression of proteins and genes related to the mitotic process, thereby affecting cell cycle, further inhibiting the proliferation of cervical cancer cells and promoting cell apoptosis [8][9][10][11][12][13][14][15][16][17] . In the study of Li et al [18] , the effect of paclitaxel chemotherapy on nude mice with cervical cancer transplantation tumors was assessed. After paclitaxel treatment, the volume of transplanted tumors in nude mice decreased significantly.…”
Section: Genementioning
confidence: 99%
“…Previous reports demonstrated that PI3K-Akt-mTOR signaling is tightly associated with EMT (26). To further investigate the mechanism of APLNR-mediated effects on EMT in NPC cells, we examined whether PI3K pathway activation occurred in response to APLNR overexpression or knockdown.…”
Section: Aplnr Inhibited Migration and Invasion Of Npc Cells By Regulmentioning
confidence: 99%